A LONGITUDINAL EVALUATION OF DEMENTIA INFORMAL CAREGIVER'S WILLINGNESS TO PAY FOR AN IN-HOME INTERVENTION. (11th November 2018) - Jutkowitz, E; Pizzi, L; Scerpella, D; Marx, K; Samus, Q; Piersol, C; Gitlin, L
Abstract: It is necessary to provide informal dementia caregivers, the largest providers of dementia care, with effective support and skills. Tailored nonpharmacologic interventions reduce behavioral symptoms, caregiver stress, and time spent caregiving. To facilitate the translation of a nonpharmacologic intervention, we evaluated how much caregivers were willing to pay (WTP) to learn strategies to manage behavioral symptoms. Caregiver/person with dementia dyads (n=223) were recruited to participate in a randomized controlled trial evaluating a nonpharmacologic intervention to minimize behavioral symptoms through the use of meaningful activities compared to attention control. At baseline, 3-months, and 6-months, a contingent valuation payment card method was used to assess how much caregivers would be WTP per session for an 8-session 3-month nonpharmacologic program delivered in-home to address behavioral problems. We calculated unadjusted WTP at each time point. A linear mixed-effects model was used to evaluate WTP within and between treatment groups WTP over time. The model controlled for key baseline covariates including age, gender, race, and cognition of the person with dementia and the relationship between the caregiver and person with dementia. At baseline, mean WTP was 35.34 (SD=56.29) per session. Mean per session WTP at 3-months (34.87 SD=61.34) and 6-months (26.59 SD=37.06) were consistent. In the linear mixed-effects model, no significant within or between group differences were observed. Informal family caregivers are consistent in their assessment of WTP before and after exposure to a nonpharmacologic intervention. The monetary value that caregivers place on in-home skills interventions is important to informing payment models for these programs.